Selecting sheep for Haemonchus contortus resistance and susceptibility: Flock dynamics and genetic architecture. (October 2020) - Gowane, G.R.; Swarnkar, C.P.; Misra, S.S.; Kumar, Rajiv; Kumar, Arun; Singh, D.; Prince, L.L.L.
Abstract: The study was carried out in the selected strains of Malpura and Avikalin sheep for nematode resistance versus susceptibility (Malpura resistant: MR, Malpura susceptible: MS, Avikalin resistant: AR and Avikalin susceptible: AS). Strains were selected since 2004 and inter-se breeding followed since year 2007. The objective was to decipher the genetic structure of strains and to estimate genetic parameters for fecal egg count (FEC). The population size was small (107–279); however, all the four flocks had sizable effective population size ( f e ) for founders. The ratio for f e to effective number of ancestors ( f a ) was nearly 1 indicating genetic stability. Inbreeding was under control. The log transformed FEC (LFEC) was significantly ( P < .05) affected by sex, year and month of recording for all 4 strains. Generation had desired genetic trend. There was low heritability for LFEC in MR(0.02), MS(0.06), AR(0.07) and AS(0.02). The estimate of the permanent environment effect (c 2 ) was low. Repeatability (ρ) for LFEC were 0.05, 0.11, 0.07 and 0.06 for MR, MS, AR and AS, respectively. Pruning the data for repeated records in peak infection period (1: "Aug-Sep" and 2: only "Sep") resulted in considerable increase in ρ for MR (Aug-Sep: 0.07 ± 0.03 and Sep: 0.12 ± 0.07) and AR (Aug-Sep: 0.05 ± 0.04 and Sep: 0.09 ± 0.10). Results revealed genotype x environment interaction for repeated measures across months. Low flock size and low genetic variability are hurdles for improvement in R strains. It is recommended to incorporate new candidates post selection from the other breeding flocks and admit them in the R strains for selective breeding. Highlights: Divergent sheep strains for resistance and susceptibility to H. contortus were developed. Fecal egg count was significantly (P < .05) affected by sex, year and month of recording. The h 2 for FEC was low and there is a need to increase the flock size of resistant strain. Repeatability for across-year FEC was low, however, for peak infection period it increased. Results revealed genotype x environment interaction for repeated measures across months.